Решите уравнение tgx-sinx=1-tgx*sinx

решите уравнение tgx-sinx=1-tgx*sinx

    sinx-sinx*cosx=cosx-sinx*sinx

    x2=3/2ПИ+2ПИb. b принадлежит Z

     

    1) sinx-cosx=0 или 2) 1+sinx=0

    1) sinx-cosx=0 (делим на cosx - не равен 0)

    ОДЗ x не = ПИ/2+ПИt. t принадлежит Z

    sinx-sinx*cosx-cosx+sinx*sinx=0 далее групируем

    tgx=1

    sinx/cosx-sinx=1-sinx*sinx/cosx (Все умножаем на cosx - не равен 0)

    x=ПИ/4+2ПИn, n принадлежит Z

    tgx-1=0

    sinx=-1

  • tgx-sinx=1-tgxsinx

    x1=- ПИ/2+2ПИm. m принадлежит Z

    2) 1+sinx=0

    sinx(1+sinx)-cosx(sinx+1)=0

    (sinx-cosx)(1+sinx)=0